PENGEMBANGAN E-LKPD BERBASIS WIZER.ME BERMUATAN BUDAYA LOKAL DALAM PEMBELAJARAN MENYIMAK SISWA KELAS II SDS KRISTEN SUNGAI KEHIDUPAN - Sonia Miranda Simorangkir; Halimatussakdiah (STKIP Subang, 2026)
This research was conducted to develop E-LKPD based on wizer.me containing local culture in listening learning for second-grade students, especially simple text materials. The aspects assessed include the feasibility, practicality and effectiveness of the developed product. This research uses the ADDIE development model which includes the stages of analysis, design, development, implementation and evaluation. The subjects of the research were second-grade students of Sungai Kehidupan Christian Elementary School consisting of 24 students. The instruments used in this research include expert validation sheets, questionnaires from educational practitioners (teachers) and listening performance tests equipped with listening assessment rubrics. Data analysis techniques used include analysis of feasibility, practicality and effectiveness data. The results showed that the results of the material and language validation percentage in stage I were 80% in stage II 90%, the percentage of design validation in stage I 80% in stage II 88.33%, the percentage of assessment rubrics in stage I 78.3% in stage II 90. The results of the practicality percentage were 89.23%. The results of the effectiveness percentage were seen from the comparison between the average pretest score and the average posttest score. The average pretest score was 47.08, and the average posttest score was 80.41. Thus, the e-LKPD developed based on wizer.me containing local culture in listening learning for second graders at Sungai Kehidupan Christian Elementary School is declared very feasible in terms of material and language, design, and assessment rubrics. It is very practical and effective for use in listening learning, especially listening to simple texts in second graders at Sungai Kehidupan Christian Elementary School.